Personal reflections on 50 years of scientific computing: 1967–2017. Issue 2 (3rd March 2020) - Watson, Layne T.
Abstract : Computer hardware, software, numerical algorithms, and science and engineering applications are traced for a half century from the author's perspective. GRAPHICAL ABSTRACT: